One dose, one billion girls: the scientific and public health imperative of India’s single dose human Papillomavirus vaccination strategy - Meenakshi Khapre; Anjali Mukkunnoth (International Journal Of Community Medicine And Public Health, 2026)
Cervical cancer remains one of the leading causes of cancer mortality in women across low- and middle-income countries (LMICs). In India, an estimated 1,27,526 new cases and 79,906 deaths were recorded in 2022, accounting for approximately 19% of the global burden.1 Every day, nearly 200 Indian women lose their lives to a disease that a vaccine can prevent. Against this backdrop, the phased introduction of the human Papillomavirus (HPV) vaccine under India's Universal Immunisation Programme (UIP), following the Union Budget announcement in February 2024 and sustained advocacy by the National Technical Advisory Group on Immunisation (NTAGI), represents a watershed moment in preventive oncology.